SAMPLING THE CAPE VERDE MANTLE PLUME: EVOLUTION OF MELT COMPOSITIONS ON SANTO ANTAO, CAPE VERDE ISLANDS - Holm P.M.; Wilson J.R.; Christensen B.P.; Hansen L.; Hansen S.L.; Hein K.M.; Mortensen A.K.; Pedersen R.; Plesner S.; Runge M.K. (My University, 2006)
The volcanic history of Santo Antao, NW Cape Verde Islands, includes the eruption of basanite–phonolite series magmas between 7·5 and 0·3?Ma and (melilite) nephelinite–phonolite series magmas from 0·7 to 0·1?Ma. The most primitive volcanic rocks are olivine ± clinopyroxene-phyric, whereas the more evolved rocks have phenocrysts of clinopyroxene ±Fe–Ti oxide ± kaersutite ± hauyne ± titanite ± sanidine; plagioclase occurs in some intermediate rocks. The analysed samples span a range of 19–0·03% MgO; the most primitive have 37–46% SiO2, 2·5–7% TiO2 and are enriched 50–200 ? primitive mantle in highly incompatible elements; the basanitic series is less enriched than the nephelinitic series. Geochemical trends in each series can be modelled by fractional crystallization of phenocryst assemblages from basanitic and nephelinitic parental magmas. There is little evidence for mineral–melt disequilibrium, and thus magma mixing is not of major importance in controlling bulk-rock compositions. Mantle melting processes are modelled using fractionation-corrected magma compositions; the models suggest 1–4% partial melting of a heterogeneous mantle peridotite source at depths of 90–125?km. Incompatible element enrichment among the most primitive magma types is typical of HIMU OIB. The Sr, Nd and Pb isotopic compositions of the Santo Antao volcanic sequence and geochemical character change systematically with time. The older volcanic rocks (7·5–2?Ma) vary between two main mantle source components, one of which is a young HIMU type with 206Pb/204Pb = 19·88, ?7/4 = ?5, ?8/4 ≈ 0, 87Sr/86Sr = 0·7033 and 143Nd/144Nd = 0·51288, whereas the other has somewhat less radiogenic Sr and Pb and more radiogenic Nd. The intermediate age volcanic rocks (2–0·3?Ma) show a change of sources to two-component mixing between a carbonatite-related young HIMU-type source (206Pb/204Pb = 19·93, ?7/4 = ?5, ?8/4 = ?38, 87Sr/86Sr = 0·70304) and a DM-like source. A more incompatible element-enriched component with ?7/4 > 0 (old HIMU type) is prominent in the young volcanic rocks (0·3–0·1?Ma). The EM1 component that is important in the southern Cape Verde Islands appears to have played no role in the petrogenesis of the Santo Antao magmas. The primary magmas are argued to be derived by partial melting in the Cape Verde mantle plume; temporal changes in composition are suggested to reflect layering in the plume conduit.
Keywords: radiogenic isotopes; geochemistry; mantle melting; Cape Verde